EXPLORE THE DIGITAL WORLD SAFELY AND SMARTLY FOR A BETTER FUTURE - Yanita; Taufiq; Nurmala; Likdanawati; Sullaida (RADJA PUBLIKA, 2025)
In the digital era that continues to advance, the use of information technology has become an inseparable part of everyday life, including in the field of education. However, this development also presents a number of challenges, especially for the younger generation who are still in the process of growing and searching for their identity. Many students do not fully understand the importance of ethics in the digital world, security in cyberspace, and how to use the internet wisely and positively. This activity is designed in the form of interactive socialization, short training, and discussion and question and answer sessions that involve the active participation of students. The material provided includes an introduction to the digital world, the threat of cybercrime such as online bullying, online fraud, and the spread of hoaxes, how to maintain the security of personal data, and the application of ethics in using the internet. In addition, students are also encouraged to recognize the potential of the digital world as a means of learning, channeling creativity, and developing themselves. Through a communicative and fun approach, this activity aims to encourage students to be wiser in using digital devices and social media. Participants will also be equipped with the ability to become digital literacy agents in their respective environments. This community service activity is in line with the national character building and digital literacy program, and supports the school's vision in forming a generation that is able to adapt to the development of the times without abandoning strong moral and social values. With the presence of technology, several suggestions can be put forward, one of which is the importance of early digital literacy development. Junior high school students are at an age that is vulnerable to the negative impacts of the digital world. Therefore, there needs to be routine digital literacy training and education in schools, so that students can understand both the benefits and risks of using technology. In addition, collaboration between schools and universities is also needed. Community service activities like this emphasize the importance of synergy between higher education institutions and schools in forming a generation that is literate and skilled in the digital world.